Banking of surplus emissions allowances: Does the volume matter? - Karsten Neuhoff; Anne Schopp; Rodney Boyd; Kateryna Stelmakh; Alexander Vasa (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In the European Emission Trading scheme the supply of allowances exceeds emissions - cumulating, according to our estimates, in a surplus of 2.7 billion tonnes by 2013/2014. We find that initially the surplus was acquired by power companies so as to hedge future carbon costs. As the surplus exceeds this hedging demand, additional allowances need to be acquired as speculative investment. This requires higher rates of return and implies that expected future carbon prices are highly discounted. This could explain the recent drop in carbon prices. The analysis shows that the volume of unused allowances matters for the discount applied to future carbon prices. We use our supply-demand framework to assess currently discussed policy options set-aside, reserve price for auctions and adjustments of emission targets.
Keywords: G18; Q48; 330; European emission trading scheme; banking; discount rates